Coronary CT Angiography (cCTA): Automated Registration of Coronary Arterial Trees from Multiple Phases - Hadjiiski, Lubomir (Phys Med Biol, 2014)
Coronary computed tomography angiography (cCTA) is a commonly used imaging modality for evaluation of coronary artery disease. cCTA is generally reconstructed in multiple cardiac phases because different coronary arteries may be better visualized in some phases than in other phases due to the periodic cardiac motion. We are developing an automated registration method for coronary arterial trees from multiple-phase cCTA that has potential application in building a “best-quality” tree to facilitate image analysis and detection of stenotic plaques. Given the segmented left or right coronary arterial trees (LCA or RCA) from the multiple phases as input, the adjacent phase pairs, where displacements are relatively small, are registered by specifically designed method based on cubic B-spline with fast localized optimization (CBSO). For the phase pairs with large displacements, a global registration using affine transform with quadratic terms and nonlinear simplex optimization (AQSO) is followed by a local registration using CBSO to refine the AQSO registered volumes. 26 LCA and 26 RCA trees with 6 cCTA phases from 26 patients were used for registration evaluation. The average distances for the tree pairs between the adjacent phases with small displacements before and after CBSO registration were 0.96 ± 0.79 mm and 0.76 ± 0.61 mm, respectively, for LCA and 0.93 ± 0.97 mm and 0.64 ± 0.43 mm, respectively, for RCA. The average distance differences before and after registration were statistically significant (p<0.001) for both LCA and RCA trees. The average distances for the distant phases with large displacements before registration, after AQSO registration, and finally after the CBSO registration were 2.85 ± 1.46, 1.62 ± 0.76, and 0.97 ± 0.43 mm, respectively, for LCA, and 4.03 ± 2.36, 2.18 ± 1.11, and 0.97 ± 0.44 mm, respectively, for RCA. The average distance differences between every two consecutive stages of registration were statistically significant. The corresponding phases of LCA and RCA trees were aligned to an average of less than 1 mm, providing a basis for a best-quality tree construction.